Blockchain smart contract meta-modeling - Sánchez-Gómez, Nicolás (2021)
One of the key benefits of blockchain technology is its ability to keep a permanent, unalterable record of transactions. In business environments, where companies interact with each other without a centralized authority to ensure trust between them, this has led to blockchain platforms and smart contracts being proposed as a means of implementing trustworthy collaborative processes. Software engineers must deal with them to ensure the quality of smart contracts in all phases of the smart contract lifecycle, from requirements specifications to design and deployment. This broad scope and criticality of smart contracts in business environments means that they have to be expressed in a language that is intuitive, easy-to-use, independent of the blockchain platform employed, and oriented towards software quality assurance. In this paper we present a key component: a first outline of a UML-based smart contract meta-model that would allow us to achieve these objectives. This meta-model will be enriched in future work to represent blockchain environments and automated testing.